Leaders and Battles : The Art of Military Leadership - Wood, W. J (India and U.S.A Lancer Publishers and Presidio Press, 1996)
This is one of my favorite books to reread, there are few more inspiring to me. W.J Wood takes the liberty to put the reader inside the leaders mind and provides fantastic dialogue between the commander of each battle and his subordinates. By presenting each of the battles this way, the reader may find himself there as well, or at the very least immensely captivated and learned. His book on Revolutionary War battles is worth a look as well.
Include Index, Appendix, Bibliography, Epilogue,Footnotes and Illustrations.
Keywords: Military History -- Leadership